Kualitas Pelayanan Kereta-Api Dengan Pendekatan Pengalaman Penumpang dan Dampaknya Pada Kepercayaan Penumpang - Levyda Levyda (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2021)
Passenger trust is a key factor to win the competition. This study aims to develop multi-dimensional service quality based on passenger experience which includes ticketing quality, station quality and train quality and examine the effect of service quality on passenger satisfaction and trust. This research is a quantitive research. Sampling was done by purposive sampling and the number of samples was two hundred and thirteen people. Samples were obtained by snowball sampling method/ Data processing is done by SEM Lisrel. The quality of ticketing services, service quality at stations and service quality on trains developed in this study is significant as a measure of train service quality. The quality of service on the train has a greater influence on the quality of service and is followed by the quality of service at the station and the quality of ticketing. The quality of employee service greatly determines the quality of stations and trains, while the booking process determines the quality of ticketing. The indirect effect of service quality on passenger trust through passenger satisfaction is higher than the direct effect of service quality on passenger trust.